The gender dynamics of Zimbabwe s fast track land reform programme - Madebwe, Crescentia; Madebwe, Victor (Midlands State University, 2014)
The paper explores interfaces between gender and land reform with specific reference to women s ability to access land and participate in land reform processes during the fast tract land resettlement programme in Zimbabwe. Statistics indicating beneficiaries of A1 and A2 resettlement models were abstracted from the national quantitative data base on the fast track land reform programme compiled by the Presidential Land Review Committee in 2003 and interviews with members of district and provincial land identification and allocation committees and beneficiaries of land. The paper posits that lack of a gender numeric target, diverse and non-specific land allocation criteria countrywide may have derailed women s ability to access land. Women s stake in land reform may have been compromised following the ideological transition from land reform targeting the landless to e-conceptualizing land reform to establish a new crop of indigenous large-scale farmers.